Titanium oxide powder

The hydrolysis and controlled drying process of titanium chloride with additives like urea or acids produces Anatase-type titanium oxide with high surface area and minimal impurities, addressing dispersion and composition challenges for electronic devices.

JP7626299B1Active Publication Date: 2025-02-04RESONAC CORP

Patent Information

Application Number
JP2024534148
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2025-02-04
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

Existing methods for producing titanium oxide nanoparticles for electronic devices face challenges in achieving high dispersion stability and composition control, with impurities like silicon and phosphorus affecting dielectric properties, and aggregation issues due to high surface energy.

Method used

A method involving the hydrolysis of titanium chloride using urea, ammonium compounds, inorganic acids, or organic acids, followed by controlled drying at specific relative humidity, to produce Anatase-type titanium oxide with high surface area and minimal impurities, ensuring uniform dispersion.

Benefits of technology

The method yields Anatase-type titanium oxide with enhanced dispersibility, improved affinity to solvents, and controlled composition, suitable for electronic devices without deteriorating their characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626299000001
    Figure 0007626299000001
  • Figure 0007626299000002
    Figure 0007626299000002
Patent Text Reader

Abstract

The object of the present invention is to provide an anatase type titanium oxide powder having a large specific surface area and high dispersibility, and a method for producing the same. The titanium oxide powder has a BET specific surface area of ​​300 m2 / g or more and 480 m2 / g or less as measured using a nitrogen adsorption method, an anatase content of the crystal phase of 90% or more as measured using XRD measurement, and a spin-spin relaxation time T2 of 46 ms or more and 103 ms or less as measured by pulse NMR of a 5% by mass suspension prepared in ion-exchanged water.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to titanium oxide powder. At the end Regarding. [Background technology]

[0002] Titanium dioxide (IV) (TiO2) is a chemically stable material and is used industrially in a wide range of fields, including as a white pigment. Titanium dioxide (IV) also reacts with barium carbonate to produce barium titanate, which is known to be used as a material for multilayer ceramic capacitors, which are components of smartphones and other devices. There are three known crystal structures that titanium dioxide can have: anatase, brookite, and rutile. Anatase titanium dioxide in particular has more hydroxyl groups on its surface than other crystal phases, making it highly hydrophilic and highly dispersible. In addition, because anatase titanium dioxide has many hydroxyl groups on its surface, it has high surface reactivity with other metal elements, and is in high demand as a raw material for dielectric materials and battery materials. In recent years, there has been a demand for fine anatase titanium dioxide with a high specific surface area to achieve higher functionality in these applications.

[0003] On the other hand, as the particles become finer, the surface free energy increases, which makes the particles more likely to aggregate and deteriorates dispersibility. In order to suppress the aggregation of particles, a manufacturing method has been reported in which the particle surface is modified with a modifying agent such as a silane agent, and the particles are dispersed and stabilized in a dispersion liquid containing an amine agent, as in Patent Document 1.

[0004] Generally, nanoparticles are mixed with an aqueous or alcoholic solvent, and a method is used to increase the affinity with the solvent by increasing the hydrophilicity of the particle surface. One method for increasing the hydrophilicity of the particle surface is to modify the particle surface with a polymer containing silicon, as described in Patent Documents 2 and 3. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2008-247712 A [Patent Document 2] JP 2015-212355 A [Patent Document 3] JP 2010-95392 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, although the manufacturing method of Patent Document 1 can obtain a dispersion of nanoparticles, it is difficult to control the concentration during manufacturing and storage in the form of a dispersion. Therefore, the dispersion obtained by the manufacturing method disclosed in Patent Document 1 is not suitable for producing titanium oxide for electronic device applications such as dielectric materials and battery materials, which require strict composition control. In addition, silicon and phosphorus contained in the dispersant have a significant effect on the main properties of materials for electronic devices, such as the dielectric constant and conductivity, and are therefore not suitable as electronic device materials. Moreover, the titanium oxides described in Patent Documents 2 and 3 also contain a large amount of silicon and are therefore unsuitable as materials for electronic devices.

[0007] For these reasons, there is a demand for highly dispersible ultrafine particles of anatase-type titanium dioxide in a dry powder format that can be mixed uniformly with other raw materials after rigorously calculating the composition when used as an electronic device material.In addition, in order to prevent deterioration of the properties of electronic device materials, it is also required that the fine particles of anatase-type titanium dioxide do not contain semimetallic elements such as silicon and phosphorus, metallic elements such as sodium and magnesium, or polymeric organic acid chains such as polyols.

[0008] The present invention relates to an anatase type titanium oxide powder having a high specific surface area and high dispersibility. The end The purpose is to provide. [Means for solving the problem]

[0009] The inventors have discovered that by synthesizing anatase-type titanium oxide through hydrolysis of titanium tetrachloride in the presence of a dispersant such as urea, an ammonium compound, an inorganic acid, or an organic acid, and then drying the synthesized titanium oxide in an atmosphere with an initial relative humidity of 70 to 100%, it is possible to suppress dense aggregation of particles and particle growth, and to obtain a dry powder without deactivating the hydroxyl groups on the particle surfaces, thereby obtaining anatase-type titanium oxide powder that has a high specific surface area, high affinity with solvents, and high dispersibility. In order to achieve the above object, the present invention is configured as follows.

[0010] (1) The titanium oxide powder according to one embodiment of the present invention has a BET specific surface area of ​​300 m as measured by a nitrogen adsorption method. 2 / g or more 480m 2 / g or less, the anatase content of the crystalline phase as measured using XRD measurement is 90% or more, and the spin-spin relaxation time T2 of a 5 wt% suspension prepared in ion-exchanged water as measured by pulse NMR is 46 ms or more and 103 ms or less.

[0011] (2) In the titanium oxide powder of (1) above, the carbon content may be 0.5 mass % or less.

[0012] (3) In the titanium oxide powder of (1) or (2) above, the chlorine content may be 0.1% by mass or less, the silicon content may be 0.1% by mass or less, and the sulfur content may be 0.1% by mass or less.

[0013] (4) In the titanium oxide powder of any one of (1) to (3) above, the diffraction angle 2θ may be such that the half-width of the diffraction peak at 24.5° to 26.0° is 1.10° to 2.00°.

[0014] (5) Any of the titanium oxide powders (1) to (4) above may have a zeta potential of −63 mV or more and −40 mV or less.

[0015] (6) A method for producing a titanium oxide powder according to one embodiment of the present invention includes a synthesis step of mixing an aqueous solution containing urea with an aqueous solution containing titanium tetrachloride and having a pH of less than 3 so that the urea / Ti (molar ratio) is 0.001 or more and 0.058 or less to precipitate titanium oxide, and a drying step of drying the obtained titanium oxide in an atmosphere with an initial relative humidity of 70 to 100% to powder it.

[0016] (7) A method for producing a titanium oxide powder according to one embodiment of the present invention includes a synthesis step of mixing an aqueous solution containing an ammonium compound with an aqueous solution containing titanium tetrachloride and having a pH of less than 3 so that the ammonium compound / Ti (molar ratio) is 0.001 or more and 0.029 or less to precipitate titanium oxide, and a drying step of drying the obtained titanium oxide in an atmosphere with an initial relative humidity of 70 to 100% to powder it.

[0017] (8) In the method for producing a titanium oxide powder according to (6) or (7) above, the aqueous solution containing at least one of urea and an ammonium compound may have a pH of less than 12.0.

[0018] (9) A method for producing a titanium oxide powder according to one embodiment of the present invention includes a synthesis step of mixing an aqueous solution containing an inorganic acid with an aqueous solution containing titanium tetrachloride and having a pH of less than 3 so that the inorganic acid / Ti (molar ratio) is 0.001 or more and 0.030 or less to precipitate titanium oxide, and a drying step of drying the obtained titanium oxide in an atmosphere with an initial relative humidity of 70 to 100% to powder it.

[0019] (10) A method for producing a titanium oxide powder according to one embodiment of the present invention includes a synthesis step of mixing an aqueous solution containing an organic acid with an aqueous solution containing titanium tetrachloride and having a pH of less than 3 so that the acidic functional groups of the organic acid / Ti (molar ratio) is 0.001 or more and 0.037 or less to precipitate titanium oxide, and a drying step of drying the obtained titanium oxide in an atmosphere with an initial relative humidity of 70 to 100% to powder it.

[0020] (11) In the method for producing titanium oxide powder according to (10) above, the organic acid may be an α-hydroxycarboxylic acid.

[0021] (12) In the method for producing a titanium oxide powder according to (10) or (11) above, the organic acid or inorganic acid in the aqueous solution may have a molecular weight of 300 or less.

[0022] (14) The above methods for producing titanium oxide powder (6) to (13) may further include a purification step of purifying titanium oxide using one or more of an ultrafiltration membrane, a reverse osmosis membrane, an ion exchange resin, and an electrodialysis membrane. Effect of the Invention

[0023] According to the present invention, an anatase type titanium oxide powder having a large specific surface area and high dispersibility is obtained. The end can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] An example of an embodiment of the present invention will be described below, but the present invention is not limited to the following example.

[0025] In this embodiment, "titanium oxide" refers to titanium(IV) oxide (TiO2) unless otherwise specified. Also, "Ti concentration" refers to the concentration obtained by dividing (the amount of Ti atoms taking into account all titanium-atom-containing components that constitute titanium compounds, titanium-containing ions, complexes, etc.) by (the volume of the solution containing Ti).

[0026] <1. Titanium oxide powder> The titanium oxide powder according to one embodiment of the present invention has a BET specific surface area of ​​300 m2 as measured by a nitrogen adsorption method. 2 / g or more 480m 2 / g or less, the anatase content of the crystalline phase as measured using XRD measurement is 90% or more, and the spin-spin relaxation time T2 of a 5% by mass suspension prepared using ion-exchanged water as measured by pulsed NMR (Nuclear Magnetic Resonance) is 46 ms or more and 103 ms or less.

[0027] (BET specific surface area) As described above, the BET specific surface area of ​​the titanium oxide powder according to one embodiment of the present invention is 300 m 2 / g or more. 300m 2 / g or more, when titanium oxide is reacted with other substances, it is possible to obtain ultrafine particles such as 0201 size multilayer ceramic capacitor materials. From the same viewpoint, in order to obtain ultrafine particles with a finer particle size, the BET specific surface area of ​​titanium oxide powder is 350 m 2 / g or more is preferable, and 380m 2 / g or more is more preferable.

[0028] As described above, the BET specific surface area of ​​the titanium oxide powder of one embodiment of the present invention is 480 m 2 / g or less. 2 / g or less, abnormal grain growth of titanium oxide can be suppressed even when reacted with barium carbonate at high temperatures, and the grain size distribution of the resulting barium titanate material can be made uniform. From the same perspective, in order to obtain a material with a more uniform grain size distribution, the BET specific surface area of ​​the titanium oxide powder is 430 m 2 / g or less is preferable, and 400m 2 / g or less is more preferable.

[0029] (Anatase content) In the titanium oxide powder of this embodiment, the content of the anatase phase of the crystal phase measured by XRD measurement is 90% or more. When titanium oxide is reacted with other substances, a high content of the anatase phase in the titanium oxide powder is advantageous because it increases reactivity. From the same viewpoint, the content of the anatase phase is more preferably 95% or more, and even more preferably 99% or more.

[0030] (spin-spin relaxation time) Unlike high-resolution NMR, pulsed NMR does not provide chemical shift information, but instead is a technique that can rapidly measure the relaxation times (spin-lattice relaxation time T1 and spin-spin relaxation time T2) of 1H nuclei, which are closely related to molecular mobility. The use of pulsed NMR has been rapidly expanding in recent years. Measurement methods in pulsed NMR include the Hahn echo method, the solid echo method, the CPMG method, and 90° pulsed NMR, and any of these can be suitably used. In the present invention, the spin-spin relaxation time T2 means the spin-spin relaxation time T2 of 1H nucleus measured by the CPMG method.

[0031] In the titanium oxide of this embodiment, the spin-spin relaxation time T2 of 1H nucleus measured by the CPMG method of pulse NMR while dispersed in water is considered to be a characteristic related to the state of water molecules bound to the titanium oxide surface. Specifically, the shorter the spin-spin relaxation time T2, the more water molecules bound to the titanium oxide surface (the thicker the hydration layer), and therefore the dispersibility of the titanium oxide is improved, which is thought to facilitate improvement in filtration performance.

[0032] In the titanium oxide powder according to one embodiment of the present invention, the spin-spin relaxation time T2 measured by the CPMG method of pulse NMR for a 5% suspension prepared using ion-exchanged water is 46 ms or more and 103 ms or less. If the spin-spin relaxation time T2 of the suspension is 46 ms or more, when the titanium oxide powder is reslurried to prepare a dispersion liquid to obtain barium titanate, it does not become overdispersed, and the viscosity is suppressed to an appropriate level, and the flow state is excellent, which is advantageous when reacting with other substances. From the same viewpoint, the spin-spin relaxation time T2 is preferably 60 ms or more, and more preferably 70 ms or more. If the spin-spin relaxation time T2 is 103 ms or less, the number of water molecules bound to the titanium oxide surface increases (due to the thick hydration layer), and it is considered that the dispersibility is excellent. From the same viewpoint, the spin-spin relaxation time T2 is preferably 90 ms or less, and more preferably 80 ms or less.

[0033] (Elemental analysis) It is believed that Cl (chlorine), Fe (iron), Al (aluminum), Si (silicon), and S (sulfur) cause a decrease in the dielectric constant when the titanium oxide powder according to this embodiment is used as a raw material for a dielectric material. Therefore, the chlorine content, aluminum content, silicon content, and sulfur content of the titanium oxide powder according to this embodiment are each preferably 0.1 mass% or less, more preferably 0.05 mass% or less, and even more preferably 0.01 mass% or less. There is no particular restriction on the lower limit, but from the viewpoint of the cost of the production method, 0.0001 mass% or more is preferable.

[0034] In order to suppress the precipitation of by-products derived from C (carbon), the carbon content of the titanium oxide according to one embodiment of the present invention is preferably 0.50% by mass or less, more preferably 0.30% by mass or less, and even more preferably 0.10% by mass or less. There is no particular restriction on the lower limit, but from the viewpoint of the cost of the production method, it is preferably 0.001% by mass or more.

[0035] (Half-width of diffraction peak in crystalline X-ray diffraction measurement) The full width at half maximum (FWHM) of the diffraction peak appearing in the range of 24.5° to 26.0° of the diffraction angle 2θ obtained by the X-ray diffraction (XRD) measurement of the titanium oxide powder of this embodiment is preferably 1.10° or more. In this case, the smaller the FMHM of the titanium oxide powder, the higher the crystallinity, and this is preferable, but in order to make the FMHM very small, the titanium oxide powder is reacted at a high temperature, and this tends to cause aggregation of the titanium oxide powder, resulting in a small BET specific surface area. Therefore, from the viewpoint of obtaining titanium oxide powder that is not very aggregated, it is desirable to set the FMHM to a certain value or more, and preferably 1.10° or more. From the same viewpoint, the FWHM is more preferably 1.30° or more, and even more preferably 1.50° or more.

[0036] The FWHM is preferably 2.00° or less. This is because the better the crystallinity of titanium oxide, the better the crystallinity of products produced using titanium oxide. From the same viewpoint, it is more preferably 1.90° or less, and even more preferably 1.80° or less.

[0037] The titanium oxide powder according to one embodiment of the present invention has the above-mentioned configuration and has a zeta potential of -63 mV or more and -40 mV or less. That is, the absolute value of the zeta potential of the titanium oxide powder according to this embodiment is 40 mV or more and 63 mV or less. In this way, the titanium oxide powder according to one embodiment of the present invention has a large zeta voltage and therefore has high dispersibility, and since the zeta potential is not excessive, it is possible to suppress overdispersion when attempting to prepare barium titanate, which causes the dispersion liquid to have an excessive viscosity and thus causes poor flow.

[0038] <2. Titanium oxide powder manufacturing method 1> Hereinafter, a method for producing titanium oxide powder according to the above embodiment will be described. The method for producing titanium oxide powder according to one embodiment of the present invention includes a synthesis step and a drying step. The synthesis step is a step of mixing an aqueous solution containing any one selected from the group consisting of urea, an ammonia compound, an organic acid, and an inorganic acid with an aqueous solution containing titanium tetrachloride and having a pH of less than 3 to precipitate titanium oxide. In the synthesis step, (i) when an aqueous solution containing urea is used, the mixture is made so that the urea / Ti (molar ratio) is 0.001 or more and 0.058 or less, (ii) when an aqueous solution containing an ammonia compound is used, the mixture is made so that the urea / Ti (molar ratio) is 0.001 or more and 0.029 or less, (iii) when an aqueous solution containing an inorganic acid is used, the mixture is made so that the inorganic acid / Ti (molar ratio) is 0.001 or more and 0.030 or less, and (iv) when an aqueous solution containing an organic acid is used, the mixture is made so that the acidic functional group of the organic acid / Ti (molar ratio) is 0.001 or more and 0.037 or less. In the drying process, the obtained titanium oxide is dried in an atmosphere with an initial relative humidity of 70 to 100% to be powdered.

[0039] First, as Production Method 1, a method for producing titanium oxide powder using urea as an additive to an aqueous titanium tetrachloride solution will be described.

[0040] The method for producing titanium oxide powder according to this embodiment includes a synthesis step of mixing an aqueous solution containing urea with an aqueous solution containing titanium tetrachloride and having a pH of less than 3 so that the molar ratio (urea [mol] / Ti [mol]) is 0.001 or more and 0.058 or less to precipitate titanium oxide, and a drying step of drying the obtained titanium oxide in an atmosphere with an initial relative humidity of 70 to 100% to powder it.

[0041] <2-1. Synthesis process> As described above, first, an aqueous solution containing urea and an aqueous solution containing titanium tetrachloride are mixed to obtain an aqueous solution. Hereinafter, the aqueous solution obtained by mixing may be referred to as a mixed solution. In the synthesis process, hydrolysis of titanium tetrachloride proceeds. The aqueous solution containing titanium tetrachloride has a pH value of less than 3. This is to allow the hydrolysis reaction to proceed preferentially. The aqueous solution containing titanium tetrachloride has a pH value of more preferably 2 or less, more preferably 1 or less, and for example, 0.1 or more.

[0042] Urea acts as a reaction inhibitor. The addition of urea slows down the generation of titanium oxide particles, inhibiting the phase transition to the rutile phase and suppressing aggregation.

[0043] The aqueous solution containing urea preferably has a pH of less than 12.0. At a pH of less than 12.0, the hydrolysis reaction occurs quickly, making it difficult to generate heterogeneous phases including the brookite phase, and titanium oxide gradually precipitates and is easily dispersed. From the same viewpoint, the pH is more preferably 11.5 or less, and even more preferably 11.0 or less. In addition, it is preferable that the pH is greater than 10, that is, the pH is a value exceeding 10. This is to sufficiently suppress the rate of the hydrolysis reaction and suppress the phase transition to the stable rutile phase.

[0044] The Ti atom concentration in the aqueous solution (mixture) obtained by mixing an aqueous solution containing urea and an aqueous solution containing titanium tetrachloride is preferably 0.01 mol / L or more. This is to allow the hydrolysis reaction to proceed preferentially. From the same viewpoint, the Ti atom concentration is more preferably 0.03 mol / L or more, and even more preferably 0.05 mol / L or more. The Ti atom concentration in the mixed solution is preferably 1.00 mol / L or less. This is because suppressing the Ti concentration prevents the precipitation of the stable rutile phase. From the same viewpoint, it is more preferably 0.50 mol / L or less, and even more preferably 0.20 mol / L or less.

[0045] Regarding the content of urea in the mixed solution, the ratio of the amount of urea to the amount of Ti in the mixed solution (urea [mol] / Ti [mol]) is 0.001 or more. This is to sufficiently slow down the rate of the hydrolysis reaction and suppress the phase transition of the stable phase to the rutile phase. From the viewpoint of further suppressing the phase transition to the rutile phase, the above ratio (urea [mol] / Ti [mol]) is preferably 0.013 or more, more preferably 0.030 or more. The above ratio (urea [mol] / Ti [mol]) is 0.058 or less, preferably 0.050 or less. This is to prevent the hydrolysis reaction from being excessively suppressed.

[0046] The mixed solution is preferably heated to precipitate titanium oxide. It is preferable to heat the mixed solution at a high heating rate from the viewpoint of productivity. On the other hand, in order to suppress the precipitation of amorphous titanium oxide and improve crystallinity, it is preferable to suppress the rapid progress of the reaction and to suppress the heating rate so as to allow sufficient crystal growth. Therefore, the mixed solution is preferably heated at a heating rate of 0.1° C. / min to 1.5° C. / min until the target temperature, i.e., the synthesis temperature, is reached, and the heating rate is more preferably 0.3° C. / min to 1.0° C. / min, and even more preferably 0.6° C. / min to 1.0° C. / min.

[0047] The synthesis temperature is preferably 50°C or higher, more preferably 60°C or higher. This is to allow the hydrolysis reaction to proceed preferentially. The synthesis temperature is preferably 100°C or lower. This is to suppress the phase transition from the stable phase to the rutile phase.

[0048] The time for which the mixture is held at the synthesis temperature can be set arbitrarily, and the temperature may be lowered without holding, or may be held for a predetermined time. The time for which the mixture is held at the synthesis temperature is preferably 15 minutes or more from the viewpoint of sufficiently proceeding with the reaction. After the reaction is completed, it is preferable to leave it to cool down to room temperature.

[0049] <2-2. Purification process> The method for producing titanium oxide powder according to one embodiment of the present invention preferably includes a purification step of purifying titanium oxide. The purification step uses, for example, one or more of an ultrafiltration membrane, a reverse osmosis membrane, an ion exchange resin, and an electrodialysis membrane. The method for producing titanium oxide powder according to one embodiment of the present invention further includes a purification step, which makes it possible to remove Cl (chlorine), S (sulfur), Si (silicon), Fe (iron), Al (aluminum), and the like from the slurry containing titanium oxide obtained in the synthesis step. The purification step is carried out after the synthesis step. Since the purification step is carried out in a state where titanium oxide is dispersed in a liquid, it is preferable to carry out the purification step before the drying step.

[0050] <2-3. Dehydration process> The method for producing titanium oxide powder according to one embodiment of the present invention may further include a dehydration step in which the slurry is dehydrated using a filter press or the like to obtain a solid content. The dehydration step is carried out, for example, after the synthesis step and before the drying step. When the method for producing titanium oxide powder includes a purification step, the dehydration step is carried out after the purification step. By carrying out the dehydration step, the drying step can be carried out efficiently.

[0051] <2-4. Drying process> The method for producing titanium oxide powder according to one embodiment of the present invention includes a drying process (drying step) in which the obtained titanium oxide is dried and powdered in an atmosphere with an initial relative humidity of 70 to 100%. Note that the initial relative humidity is the relative humidity at the start of the drying process. The drying atmosphere may be air or an inert gas atmosphere.

[0052] Titanium oxide may be dried in the form of a slurry in which it is dispersed or dissolved in water, or it may be dried after being dehydrated using a filter press or the like.

[0053] In the drying process, in order to remove moisture while suppressing the deactivation of hydroxyl groups on the titanium oxide surface, drying is performed in an atmosphere with an initial relative humidity of 70% or more and 100% or less. From the same viewpoint, a humidity of 75% or more is preferable, a humidity of 80% or more is more preferable, and a humidity of 90% or more is even more preferable. The initial relative humidity in the drying process may be 99% or less, or may be 97% or less. It is preferable to dry in an atmosphere with an initial relative humidity of 70% or more for a certain period of time, and then perform a drying process in the air after the passage of a certain period of time, in order to promote drying. The process of maintaining an initial relative humidity of 70% or more is also called an aging process. The aging process time is preferably 3 to 48 hours, more preferably 5 to 30 hours.

[0054] In the drying process, for example, the obtained sample is dried until the moisture content becomes 2% by mass to 15% by mass to obtain a titanium oxide solid content. The obtained oxide solid content is pulverized in a mortar or the like to obtain a titanium oxide powder.

[0055] <3. Titanium oxide powder manufacturing method 2> Next, as Production Method 2, a method for producing titanium oxide powder using an ammonium compound as an additive to an aqueous titanium tetrachloride solution will be described.

[0056] The method for producing titanium oxide powder (production method 2) according to another embodiment of the present invention includes a synthesis step of mixing an aqueous solution containing an ammonium compound with an aqueous solution containing titanium tetrachloride and having a pH of less than 3 so that the molar ratio (ammonium compound [mol] / Ti [mol]) is 0.001 to 0.029 to precipitate titanium oxide, and a drying step of drying the obtained titanium oxide under an atmosphere of initial relative humidity of 70 to 100% to powderize it. The initial relative humidity in the drying step is preferably 70% or more. The method for producing titanium oxide powder according to this embodiment differs from the method for producing titanium oxide powder according to the above embodiment (production method 1) in the conditions of the synthesis step. In the method for producing titanium oxide powder according to this embodiment, the steps other than the synthesis step can be the same as the method for producing titanium oxide powder according to the above embodiment. That is, in the production method 2, either or both of the purification step and the dehydration step may be performed between the synthesis step and the drying step. In addition, the preferred conditions for the purification step, the dehydration step, and the drying step can be the same as those of the production method 1. In the following, among the methods for producing titanium powder according to this embodiment, the conditions of the synthesis step that differ from Production Method 1 will be described.

[0057] Ammonium compounds act as reaction inhibitors. Adding them can slow down the generation of titanium oxide particles, inhibiting the phase transition to the rutile phase and inhibiting aggregation. Preferred ammonium compounds are ammonia, ammonium chloride, and ammonium carbonate, of which ammonium carbonate is particularly preferred. Ammonium carbonate is easy to adjust to the desired pH, making it possible to produce titanium oxide powder under ideal conditions.

[0058] Regarding the content of the ammonium compound in an aqueous solution (mixture) obtained by mixing an aqueous solution containing an ammonium compound with an aqueous solution containing titanium tetrachloride and having a pH of less than 3, the ratio of the amount of substance of the ammonium compound to the amount of substance of Ti in the mixture (ammonium compound [mol] / Ti [mol]) is preferably 0.001 or more. This is to sufficiently lower the rate of the hydrolysis reaction and suppress the phase transition of the stable phase to the rutile phase. From the viewpoint of further suppressing the phase transition to the rutile phase, the ratio of the amount of substance is more preferably 0.005 or more, and even more preferably 0.013 or more. The ratio of the amount of substance (ammonium compound [mol] / Ti [mol]) is preferably 0.029 or less. This is to prevent the hydrolysis reaction from being excessively suppressed. From the same viewpoint, it is more preferably 0.020 or less.

[0059] <4. Titanium oxide powder manufacturing method 3> Next, as Production Method 3, a method for producing titanium oxide powder using an aqueous solution containing an inorganic acid as an additive to an aqueous titanium tetrachloride solution will be described.

[0060] A method for producing titanium oxide powder other than the production methods 1 and 2 according to one embodiment of the present invention includes a synthesis step of mixing an aqueous solution containing an inorganic acid with an aqueous solution containing titanium tetrachloride and having a pH of less than 3 so that the molar ratio (inorganic acid [mol] / Ti [mol]) is 0.001 to 0.030 to precipitate titanium oxide, and a drying step of drying the obtained titanium oxide under an atmosphere of initial relative humidity of 70 to 100% to powderize it. The initial relative humidity in the drying step is preferably 70% or more, more preferably 75% or more, and even more preferably 80% or more. The method for producing titanium oxide powder of this embodiment has different conditions for the synthesis step from the method for producing titanium oxide powder of the above embodiment (production method 1). In the method for producing titanium oxide powder of this embodiment, the steps other than the synthesis step can be the same as the method for producing titanium oxide powder of the above embodiment. That is, in the production method 3, either or both of the purification step and the dehydration step may be performed between the synthesis step and the drying step. In addition, the preferred conditions for the purification step, the dehydration step, and the drying step can be the same as those of the production method 1. In the following, among the methods for producing titanium oxide powder of this embodiment, the conditions of the synthesis step that differ from Production Method 1 will be described.

[0061] <4-1. Synthesis process> The aqueous solution containing titanium tetrachloride has a pH of less than 3. This is to allow the hydrolysis reaction to proceed preferentially. The pH is more preferably 2 or less, and even more preferably 1 or less.

[0062] The inorganic acid adheres to the generated titanium oxide particles to stabilize the surface and acts as a phase transition inhibitor that inhibits the phase transition from anatase phase to rutile phase. The inorganic acid modifies the titanium oxide surface. It also has the effect of inhibiting the aggregation of particles. The inorganic acid is preferably a strong inorganic acid, and sulfuric acid (molecular weight 98.08) is preferred from the viewpoint of inhibiting the phase transition to the rutile phase.

[0063] The molecular weight of the inorganic acid is preferably 300 or less. When an inorganic acid with an excessively high molecular weight is added, the inorganic acid molecule is long relative to the precipitated titanium oxide, making it difficult to uniformly modify the titanium oxide surface, and the particles may not be sufficiently dispersed. In such a case, the particles may aggregate with each other and the phase transition to the rutile phase may proceed from the aggregated surface. By setting the molecular weight of the inorganic acid to 300 or less, the inorganic acid can uniformly modify the titanium oxide surface, and the dispersibility of the particles can be improved. From the same viewpoint, the molecular weight of the inorganic acid is preferably 250 or less, more preferably 200 or less. The molecular weight of the inorganic acid is, for example, 30 or more.

[0064] The Ti concentration in the mixed solution obtained by mixing an aqueous solution containing an inorganic acid with an aqueous solution containing titanium tetrachloride and having a pH of less than 3 is preferably 0.01 mol / L or more. This is to allow the hydrolysis reaction to proceed preferentially. From the same viewpoint, the Ti concentration is more preferably 0.05 mol / L or more, and even more preferably 0.30 mol / L or more.

[0065] The Ti concentration in the mixed solution is preferably 2.00 mol / L or less in order to suppress the phase transition to the rutile phase. From the same viewpoint, the Ti concentration is more preferably 1.50 mol / L or less, and even more preferably 1.00 mol / L or less.

[0066] Regarding the content of acidic compounds in a mixed solution of an aqueous solution containing an inorganic acid and an aqueous solution containing titanium tetrachloride and having a pH of less than 3, the ratio of the amount of substance of the inorganic acid to the amount of substance of titanium (inorganic acid [mol] / Ti [mol]) (molar ratio) is 0.001 or more and 0.037 or less. This is to suppress the phase transition from anatase phase to rutile phase. From the same viewpoint, it is more preferable that it is 0.010 or more, and even more preferable that it is 0.015 or more. The above amount of substance ratio (inorganic acid [mol] / Ti [mol]) is preferably 0.030 or less. This is because adding an excessive amount of inorganic acid is likely to cause reaction inhibition.

[0067] <5. Titanium oxide powder manufacturing method 4> Next, as Production Method 4, a method for producing titanium oxide powder using an aqueous solution containing an organic acid as an additive to an aqueous titanium tetrachloride solution will be described.

[0068] The method for producing titanium oxide powder of this embodiment differs from the method for producing titanium oxide powder of the above embodiment (production method 1) in the conditions of the synthesis step. In the method for producing titanium oxide powder of this embodiment, the steps other than the synthesis step can be the same as those of the method for producing titanium oxide powder of the above embodiment. That is, in production method 3, one or both of the purification step and the dehydration step may be carried out between the synthesis step and the drying step. In addition, the preferred conditions for the purification step, the dehydration step and the drying step can also be the same as those of production method 1. Below, the conditions of the synthesis step in the method for producing titanium oxide powder of this embodiment that are different from those in production method 1 will be described.

[0069] Another method for producing titanium oxide powder according to one embodiment of the present invention, different from the production methods 1 to 3, includes a synthesis step of mixing an aqueous solution containing an organic acid with an aqueous solution containing titanium tetrachloride and having a pH of less than 3 so that the molar ratio (acidic functional groups of the organic acid [mol] / Ti [mol]) is 0.001 to 0.037 to precipitate titanium oxide, and a drying step of drying the obtained titanium oxide in an atmosphere with an initial relative humidity of 70 to 100% to powder it. The initial relative humidity in the drying step is preferably 70% or more, more preferably 75% or more, and even more preferably 80% or more.

[0070] <5-1.Synthesis process> The aqueous solution containing titanium tetrachloride has a pH of less than 3. This is to allow the hydrolysis reaction to proceed preferentially. The pH is more preferably 2 or less, and even more preferably 1 or less.

[0071] The organic acid adheres to the titanium oxide particles produced, stabilizing the surface and acting as a phase transition inhibitor that inhibits the phase transition from anatase to rutile. It also has the effect of inhibiting the aggregation of particles. The organic acid is preferably an alpha-hydroxycarboxylic acid, and malic acid (molecular weight 134.09) and citric acid (192.12) are more preferable from the viewpoint of inhibiting the phase transition to the rutile phase.

[0072] For the same reason as inorganic acids, the molecular weight of the organic acid is preferably 300 or less. That is, when an organic acid with an excessively high molecular weight is added, the molecule of the acidic compound is long relative to the precipitated titanium oxide particles, so that it is difficult to uniformly modify the titanium oxide surface, and the particles may not be sufficiently dispersed. In such a case, the particles are aggregated and the phase transition to the rutile phase proceeds from the aggregated surface. By making the molecular weight of the organic acid 300 or less, the organic acid can uniformly modify the titanium oxide surface, and the dispersibility of the particles can be improved. From the same viewpoint, the molecular weight of the acidic compound is preferably 250 or less, more preferably 200 or less. In addition, the molecular weight of the organic acid is, for example, 30 or more, and preferably 40 or more.

[0073] The Ti concentration in the mixed solution of an organic acid-containing aqueous solution and a titanium tetrachloride-containing aqueous solution having a pH of less than 3 is preferably 0.01 mol / L or more. This is to allow the hydrolysis reaction to proceed preferentially. From the same viewpoint, the Ti concentration is more preferably 0.05 mol / L or more, and even more preferably 0.30 mol / L or more. The Ti concentration is preferably 2.00 mol / L or less in order to suppress the phase transition to the rutile phase. From the same viewpoint, the Ti concentration is more preferably 1.50 mol / L or less, and even more preferably 1.00 mol / L or less.

[0074] Regarding the content of the acidic functional group of the organic acid in the mixed solution of an aqueous solution containing an organic acid and an aqueous solution containing titanium tetrachloride and having a pH of less than 3, the ratio of the amount of substance of the acidic functional group of the organic acid to the amount of substance of Ti in the mixed solution (acidic functional group of organic acid [mol] / Ti [mol]) (molar ratio) is preferably 0.001 or more and 0.037 or less. This is to suppress the phase transition from anatase phase to rutile phase. From the same viewpoint, it is more preferable that it is 0.010 or more, and even more preferable that it is 0.015 or more. The above-mentioned ratio of the amount of substance (amount of substance of acidic functional group of organic acid [mol] / Ti [mol]) is preferably 0.037 or less. This is because reaction inhibition is likely to occur when an organic acid is added in large excess. From the same viewpoint, it is more preferable that it is 0.030 or less.

[0075] Here, the amount of the acidic functional group of the organic acid in the mixture represents the sum of the amounts of the acidic functional groups of the organic acid contained in the mixture. For example, if the organic acid contained in the mixture is only 1 [mol] of citric acid, the amount of the acidic functional groups of the organic acid in the mixture is 3 [mol] because citric acid has three acidic functional groups.

[0076] According to the above embodiment, anatase-type titanium oxide is synthesized through hydrolysis of titanium tetrachloride in the presence of a dispersant such as urea, an ammonium compound, an inorganic acid, or an organic acid, and the synthesized titanium oxide is dried in an atmosphere with an initial relative humidity of 70 to 100%, thereby making it possible to suppress dense aggregation between particles and grain growth, and to obtain a dry powder without deactivating the hydroxyl groups on the particle surfaces, thereby providing anatase-type titanium oxide powder that has a high specific surface area, high affinity with solvents, and high dispersibility. EXAMPLES

[0077] Examples and comparative examples of the present invention will be described below, but they do not limit the technical scope of the present invention.

[0078] <Example 1> A urea solution adjusted to pH=11 with ammonia water was added to a titanium tetrachloride aqueous solution (pH:0.8) with a Ti concentration of 15 mass% (titanium tetrachloride concentration of 59 mass%) kept at 20°C to obtain a mixed solution with a Ti molar concentration of 0.096 mol / L and (amount of urea [mol] / amount of Ti [mol]) of 0.026. The liquid temperature was always kept at 20°C during this preparation process. The mixture was then transferred to a glass reactor. Next, the mixture was heated to 60° C. at a heating rate of 0.4° C. / min using an external heater while being stirred at 60 rpm, and was maintained at that temperature for 30 minutes. Thereafter, the reaction liquid was allowed to cool to room temperature (25° C.) to obtain a slurry. After cooling, the slurry was neutralized with ammonia water, filtered and recovered using an ultrafiltration membrane (Microza UF (registered trademark) manufactured by Asahi Kasei Corporation), and washed with ion-exchanged water. The washed slurry was dewatered using a filter press to a solids content of 30% by weight. The titanium oxide solid obtained by dehydration was placed in a container with an air atmosphere and an initial relative humidity of 80% for 24 hours for aging treatment, and then dried in air until the moisture content reached 10% by mass to obtain a titanium oxide solid. This solid was pulverized in a mortar to obtain a titanium oxide powder.

[0079] <Example 2> Titanium oxide powder was obtained under the same conditions as in Example 1, except that the molar concentration of Ti in the mixed liquid was not changed and the conditions of the adjustment process were changed so that (amount of urea [mol] / amount of Ti [mol]) was 0.042.

[0080] <Example 3> Titanium oxide powder was obtained under the same conditions as in Example 1, except that the molar concentration of Ti in the mixed liquid was not changed and the conditions of the adjustment process were changed so that (amount of urea [mol] / amount of Ti [mol]) was 0.053.

[0081] <Example 4> An aqueous solution of ammonium carbonate adjusted to pH=11 was added to an aqueous solution of titanium tetrachloride (pH:0.8) with a Ti concentration of 15% by mass (a titanium tetrachloride concentration of 59% by mass) kept at 20°C to obtain a mixed solution with a Ti molar concentration of 0.096 mol / L and (amount of substance of ammonium compound [mol] / amount of substance of Ti [mol]) of 0.010. The liquid temperature was always kept at 20°C during this preparation process. The mixture was then transferred to a glass reactor. Next, the mixture was heated to 60°C at a heating rate of 0.4°C / min using an external heater while being stirred at 60 rpm using a stirrer, and was maintained at that temperature for 30 minutes. Thereafter, the reaction liquid was allowed to cool to room temperature (25°C) to obtain a slurry. Next, the slurry after cooling was neutralized with ammonia water, filtered and recovered using an ultrafiltration membrane ("Microza UF (registered trademark)" manufactured by Asahi Kasei Corporation), and washed with ion-exchanged water. The washed slurry was dewatered using a filter press to a solids content of 30% by weight. The titanium oxide solid obtained by dehydration was placed in a container with an air atmosphere and an initial relative humidity of 80% and aged for 24 hours, and then dried in air until the moisture content reached 10% by mass to obtain a titanium oxide solid. This solid was pulverized in a mortar to obtain a titanium oxide powder.

[0082] <Example 5> Titanium oxide powder was obtained under the same conditions as in Example 4, except that the molar concentration of Ti in the mixed liquid was not changed and the conditions of the adjustment process were changed so that (amount of ammonium compound [mol] / amount of Ti [mol]) was 0.016.

[0083] <Example 6> Aqueous sulfuric acid solution was added to a titanium tetrachloride aqueous solution (pH: 0.7) with a Ti concentration of 15 mass% (titanium tetrachloride concentration of 59 mass%) kept at 20°C to obtain a mixed solution with a Ti molar concentration of 0.074 mol / L and (amount of substance [mol] of inorganic acid / amount of substance [mol] of Ti) of 0.026. The liquid temperature was always kept at 20°C during this preparation process. The mixture was then transferred to a glass reactor. Next, the mixture was heated to 80°C at a heating rate of 0.2°C / min using an external heater while being stirred at 60 rpm using a stirrer, and was maintained at that temperature for 30 minutes. Thereafter, the reaction liquid was allowed to cool to room temperature (25°C) to obtain a slurry. Next, the slurry after cooling was neutralized with ammonia water, filtered and recovered using an ultrafiltration membrane ("Microza UF (registered trademark)" manufactured by Asahi Kasei Corporation), and washed with ion-exchanged water. The washed slurry was then dewatered using a filter press to a solids content of 30% by weight. The titanium oxide solid obtained by dehydration was then placed in a container with an air atmosphere and an initial relative humidity of 80% for aging treatment for 24 hours, and then dried in air until the moisture content reached 10% by mass to obtain a titanium oxide solid. This solid was pulverized in a mortar to obtain a titanium oxide powder.

[0084] <Example 7> Titanium oxide powder was obtained under the same conditions as in Example 6, except that the molar concentration of Ti in the mixed liquid was not changed and the conditions of the adjustment process were changed so that (amount of inorganic acid [mol] / amount of Ti [mol]) was 0.027.

[0085] <Example 8> Titanium oxide powder was obtained under the same conditions as in Example 6, except that the molar concentration of Ti in the mixed liquid was not changed and the conditions of the adjustment process were changed so that (amount of inorganic acid [mol] / amount of Ti [mol]) was 0.029.

[0086] <Example 9> Titanium oxide powder was obtained in the same manner as in Example 6, except that in the adjustment process, an aqueous citric acid solution was used instead of sulfuric acid, the mixed liquid was prepared so that the Ti molar concentration was 0.074 mol / L and the (amount of substance [mol] of acidic functional group of organic acid / amount of substance [mol] of Ti) was 0.022, and the initial relative humidity of the container when drying the titanium oxide solid obtained by dehydration to obtain titanium oxide solid content was changed to 95%.

[0087] <Example 10> Titanium oxide powder was obtained under the same conditions as in Example 9, except that the molar concentration of Ti in the mixed liquid was not changed and the conditions of the adjustment process were changed so that (amount of substance [mol] of acidic functional group of organic acid / amount of substance [mol] of Ti) was 0.034.

[0088] <Example 11> Titanium oxide powder was obtained in the same manner as in Example 9, except that in the adjustment process, malic acid was used instead of citric acid, and the mixed liquid was prepared so that the Ti molar concentration was 0.074 mol / L and the (amount of substance [mol] of acidic functional group of organic acid / amount of substance [mol] of Ti) was 0.026.

[0089] <Example 12> Titanium oxide powder was obtained under the same conditions as in Example 11, except that the molar concentration of Ti in the mixed liquid was not changed and the conditions of the adjustment process were changed so that (amount of substance [mol] of acidic functional group of organic acid / amount of substance [mol] of Ti) was 0.036.

[0090] <Comparative Example 1> Titanium oxide powder was obtained in the same manner as in Example 1, except that in the preparation step, no urea aqueous solution was used, and a titanium tetrachloride aqueous solution (Ti molar concentration 0.096 mol / L) with a Ti concentration of 15 mass% (titanium tetrachloride concentration 59 mass%) was used instead of the mixed liquid.

[0091] <Comparative Example 2> Titanium oxide powder was obtained under the same conditions as in Example 1, except that the molar concentration of Ti in the mixed liquid was not changed and the conditions of the adjustment process were changed so that (amount of urea [mol] / amount of Ti [mol]) was 0.063.

[0092] <Comparative Example 3> Titanium oxide powder was obtained under the same conditions as in Example 4, except that the titanium tetrachloride aqueous solution used for mixing was changed to one with a pH of 0.9, and the conditions of the adjustment process were changed so that the molar concentration of Ti in the mixed solution was not changed but the (amount of substance of ammonium compound [mol] / amount of substance of Ti [mol]) was 0.033.

[0093] <Comparative Example 4> Titanium oxide powder was obtained in the same manner as in Example 6, except that in the preparation step, a urea aqueous solution was not used, and a titanium tetrachloride aqueous solution (Ti molar concentration 0.074 mol / L) with a Ti concentration of 15 mass% (titanium tetrachloride concentration 59%) was used instead of the mixed liquid, and that the initial relative humidity of the container when the titanium oxide solid obtained by dehydration was wet-dried to obtain titanium oxide solid content was changed to 80%. <Comparative Example 5> Titanium oxide powder was obtained under the same conditions as in Example 6, except that the initial relative humidity of the container when the titanium oxide solid obtained by dehydration was dried to obtain the titanium oxide solid content was changed to 0%. That is, in Comparative Example 5, the titanium oxide solid obtained by dehydration was dry-dried. <Comparative Example 6> Titanium oxide powder was obtained under the same conditions as in Example 6, except that the initial relative humidity of the container when the titanium oxide solid obtained by dehydration was wet-dried to obtain titanium oxide solids was changed to 30%.

[0094] <Comparative Example 7> Titanium oxide powder was obtained under the same conditions as in Example 6, except that the molar concentration of Ti in the mixed liquid was not changed, and the conditions of the adjustment process were changed so that (amount of substance [mol] of inorganic acid / amount of substance [mol] of Ti) was 0.031, and the initial relative humidity of the container when wet-drying the titanium oxide solid obtained by dehydration to obtain the titanium oxide solid content was changed to 80%.

[0095] <Comparative Example 8> Titanium oxide powder was obtained in the same manner as in Example 9, except that in the preparation process, no citric acid aqueous solution was used, and a titanium tetrachloride aqueous solution (Ti molar concentration 0.096 mol / L) with a Ti concentration of 15 mass% (titanium tetrachloride concentration 59%) was used instead of the mixed liquid.

[0096] <Comparative Example 9> The titanium oxide solid obtained by dehydration was dried to obtain titanium oxide powder under the same conditions as in Example 9, except that the initial relative humidity of the container when obtaining the titanium oxide solid content was changed to 0%.

[0097] <Comparative Example 10> The titanium oxide solid obtained by dehydration was dried to obtain titanium oxide powder under the same conditions as in Example 9, except that the initial relative humidity of the container when obtaining the titanium oxide solid content was changed to 30%.

[0098] <Comparative Example 11> Titanium oxide powder was obtained under the same conditions as in Example 9, except that the molar concentration of Ti in the mixed liquid was not changed and the conditions of the adjustment process were changed so that (amount of substance [mol] of acidic functional group of organic acid / amount of substance [mol] of Ti) was 0.038. <Comparative Example 12> The titanium oxide solid obtained by dehydration was dried to obtain titanium oxide powder under the same conditions as in Example 11, except that the initial relative humidity of the container when obtaining the titanium oxide solid was changed to 0%. <Comparative Example 13> The titanium oxide solid obtained by dehydration was dried to obtain titanium oxide powder under the same conditions as in Example 11, except that the initial relative humidity of the container when obtaining the titanium oxide solid was changed to 30%.

[0099] <Comparative Example 14> Titanium oxide powder was obtained under the same conditions as in Example 11, except that the molar concentration of Ti in the mixed liquid was not changed and the conditions of the adjustment process were changed so that (amount of substance [mol] of acidic functional group of organic acid / amount of substance [mol] of Ti) was 0.045.

[0100] The preparation conditions of the titanium oxide powder in the above-mentioned Examples 1 to 12 and Comparative Examples 1 to 14 are summarized in Table 1. In Table 1, in the Comparative Examples where the additive type is indicated by "-", no additive was used, and an aqueous titanium tetrachloride solution was used instead of the mixed liquid. For convenience of explanation, Comparative Example 1, which has the same experimental data, is described in multiple places. The same applies to Comparative Example 7.

[0101]

Table 1

[0102] The titanium oxide powders of the above Examples 1 to 12 and Comparative Examples 1 to 14 were evaluated by the following evaluation methods.

[0103] <BET specific surface area> The specific surface area of the titanium oxide powder was calculated from the nitrogen adsorption / desorption curve by the BET method in accordance with JIS Z8830:2013. For the measurement of the specific surface area (BET specific surface area) by the BET method, a sample heated to 180 °C and with nitrogen gas flowing for 20 minutes as a pretreatment was measured using QUADRASORV evo manufactured by Quantachrome Corporation. The applicable range of the BET method was P / P0 = 0.00 to 0.95.

[0104] <Anatase content, rutile content> Powder X-ray diffraction measurement was performed on the titanium oxide powder, and the anatase content was calculated from the peak intensity (Ia) corresponding to the anatase-type crystal phase, the peak intensity (Ib) corresponding to the brookite-type crystal phase, and the peak intensity (Ir) corresponding to the rutile-type crystal phase. The anatase content (Anatase rate) of the crystal phase of the titanium oxide powder was calculated by the following formula. Anatase content [%] = {Ia / (Ia + Ib + Ir)} × 100 Also, the rutile content (Rutile rate) of the crystal phase of the titanium oxide powder was calculated by the following formula. Rutile content [%] = {Ir / (Ia + Ib + Ir)} × 100 Powder X-ray diffraction measurement was performed using SmartLab SE manufactured by Rigaku Corporation, and C u-Kα1 line was used, and the measurement was carried out under the conditions of tube voltage 45 kV, tube current 40 mA, measurement range 2θ = 20 to 35 [deg], sampling width 0.0167 [deg], and scanning speed 0.0192 [deg / s]. Ia: Intensity of the peak (2θ = 24.5° to 26.0°) corresponding to the anatase-type crystal phase Ir: Intensity of the peak (2θ=26.6°~28.1°) corresponding to the rutile crystal phase Ib: Intensity of the peak (2θ = 30.8° to 32.3°) corresponding to the brookite crystal phase

[0105] <Half-width of diffraction peak in crystalline X-ray diffraction measurement> Titanium oxide powder was used with Rigaku's SmartLab SE, and a copper target was used. The measurements were performed using Cu-Kα1 radiation from the University of Tokyo under conditions of a tube voltage of 45 kV, a tube current of 40 mA, a measurement range of 2θ = 24.5 to 26.0 [deg], a sampling width of 0.0167 [deg], and a scanning speed of 0.0192 [deg / s], and the FWHM of the main peak of the anatase phase near 2θ = 25° was analyzed.

[0106] In the analysis, the background was measured only in the glass cell, and the diffraction pattern of the sample was corrected by subtracting the background diffraction intensity from the diffraction intensity measured in the sample containing titanium oxide and the glass cell.

[0107] <Spin-spin relaxation time> A slurry containing 5% by mass of titanium oxide was prepared using ion-exchanged water. This slurry was filled into a disposable NMR sample tube AS1NMR manufactured by AS ONE Corporation. After filling the slurry into the sample tube, pulsed NMR measurement was immediately performed using an Acorn Area manufactured by XiGo Nanotools. The spin-spin relaxation time T2 of the titanium oxide powder was measured by pulse NMR under the following conditions. Measurement frequency: 13.1MHz, Measurement nucleus: After a single pulse irradiation at 90°, a 180° pulse was irradiated at 0.5ms intervals and the main scan was repeated four times. Measurement method: CPMG pulse sequence method, Sample volume: 0.5ml, Temperature: 23℃, Specific Surface Relaxivity (Ka):0.0075g / m 2 / ms

[0108] <Elemental analysis> The Ti, Cl, Si, Al, and Fe contents in the raw material were measured using an atomic absorption spectrometer Z-2300 manufactured by Hitachi, Ltd. after mixing the sample with an aqueous hydrogen fluoride solution and completely dissolving it using an ETHOS EASY microwave sample pretreatment device manufactured by Milestone General Co., Ltd. The Ti, Cl, Si, Al, and Fe contents in the finished titanium oxide powder were also measured using the same device after mixing the sample with an aqueous hydrogen fluoride solution and completely dissolving it in the solution. The C (carbon) and S (sulfur) in the titanium oxide powder were measured using a carbon-sulfur analyzer CS744 (manufactured by LECO).

[0109] <Moisture content measurement> Using an A&D heat-drying moisture meter MX50, 2 g of titanium oxide powder was heated to 200°C and then heated with infrared rays at 120°C until the weight change was 0.01% by mass or less, and the moisture content of the titanium oxide powder was measured.

[0110] <Zeta potential measurement> A slurry containing 0.1% by mass of titanium oxide was prepared using ion-exchanged water. The zeta potential of this slurry was measured using an ELZ-2000 made by Otsuka Electronics after filling it into a sapphire cell.

[0111] [Table 2]

[0112] Table 2 is a summary of the physical properties of the titanium oxide powders of Examples 1 to 12 and Comparative Examples 1 to 14. In the contents in Table 2, the symbol "<" is used in some places, which indicates that the value is less than the numerical value following the "<". For example, the Fe content in Comparative Example 1 is less than 0.002 mass%. As shown in Table 2, the titanium oxide powders of Examples 1 to 12 have absolute zeta potential values ​​of 42 to 63 mV. Titanium oxides within this range have good dispersibility and do not become overdispersed or cause poor flow, making them suitable for the synthesis of dielectric materials and battery materials. On the other hand, the titanium oxide powders of Comparative Examples 1 to 6 and 8 to 13 have an absolute value of zeta potential of 39 mV or less. It is known that a small absolute value of zeta potential leads to poor dispersibility and easy aggregation of particles, and these titanium oxides have poor dispersibility. The titanium oxide powders of Comparative Examples 7 and 14 have an absolute value of zeta potential of 66 mV or more. It is known that an absolute value of zeta potential that is too large leads to overdispersion and the viscosity of the dispersion increases too much, causing poor flow, and these titanium oxides are unsuitable for use in synthesis as a raw material for, for example, barium titanate.

[0113] Furthermore, when comparing the spin-spin relaxation times T2 of Examples 1 to 12 and Comparative Examples 1 to 14, the spin-spin relaxation times were 42 to 99 ms in Examples 1 to 14, confirming that titanium oxide powders were produced that did not become overdispersed when reslurried to form a dispersion.

[0114] By comparing the above-mentioned Examples and Comparative Examples, it was confirmed that the present invention can provide an anatase type titanium oxide powder having a large specific surface area and high dispersibility.

Claims

1. The BET specific surface area measured using the nitrogen adsorption method is 300 m 2 / g or more 480m 2 / g or less, the anatase content of the crystalline phase as measured by XRD measurement is 90% or more, and the spin-spin relaxation time T2 of a 5% by mass suspension prepared in ion-exchanged water, as measured by pulse NMR, is 46 ms or more and 103 ms or less.

2. 2. The titanium oxide powder according to claim 1, having a carbon content of 0.5 mass % or less.

3. 3. The titanium oxide powder according to claim 1 or 2, having a chlorine content of 0.1 mass% or less, a silicon content of 0.1 mass% or less, and a sulfur content of 0.1 mass% or less.

4. 3. The titanium oxide powder according to claim 1, wherein the half-value width of a diffraction peak at a diffraction angle 2θ of 24.5° to 26.0° is 1.10° to 2.00°.

5. The titanium oxide powder according to claim 1 or 2, having a zeta potential of -63 mV or more and -40 mV or less.

Citation Information

Patent Citations

  • Acicular, porous and fine-particle titanium oxide and its production

    JP1994340421A

  • Anatase-type titanium dioxide hyperfine particle, dispersion containing the same and method for producing the titanium dioxide

    JP2011063496A

  • Highly heat-resistant anatase-type titanium oxide and its manufacturing method

    JP2022140479A

  • Ultrafine particles of titanium dioxide and method for producing same

    WO2015033421A1

  • Titanium oxide production method

    WO2020170918A1

Cited By

  • Titanium oxide powder, titanium oxide slurry, and method for producing same

    WO2026133394A1